ANALISIS LIGHTING ARRESTER UNTUK MENGAMANKAN BUSBAR 150 kV TERHADAP GANGGUAN SURJA PADA GIS PECATU - I Putu Agus Kumara Putra; I Gede Dyana Arjana; Cok. Gede Indra Partha (Program Studi Teknik Elektro UNUD, 2021)
GIS (Gas Insulated Switchgear) Pecatu is one of the GI built by PT. PLN (Persero) toprovide energy continuity to its customers. In the GIS Pecatu there is no lighting arrester (LA)because the equipment in the GIS Pecatu is located indoors. Where there is only LA from thedirection of the GI Nusa Dua to the GIS Pecatu with a distance of 12.08 km, so it is necessaryto do study to find out whether the LA from the GI Nusa Dua direction to the GIS Pecatu canprotect the busbar from the traveling wave of lightning surge .The results of the analysis showed using the software simulation method that LA fromthe direction of the GI Nusa Dua to the GIS Pecatu has been able to protect the GIS Pecatubusbar. Simulation results obtained that the current passing through the 150 kV busbar of 1,219kA and the voltage on the busbar during a lightning surge of 4 kV. The voltage on the busbarand the current through the busbar during a surge is still within the tolerance of the maximumsystem voltage of 170 kV and the current ratio of 4 kA.